1997
DOI: 10.1287/mksc.16.2.97
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Utility Model of Disappointment and Regret Effects on Post-Choice Valuation

Abstract: In this paper we show that performance information about “forgone” alternatives (i.e., alternative that were considered but not chosen) can have a significant impact on post-choice valuation. Our approach introduces a new and parsimonious way of looking at satisfaction that combines the literature on post-choice valuation with research regarding generalized expected utility theory. While the post-valuation literature focuses on the selected brand as the valuation's basis (e.g., Anderson and Sullivan [Anderson,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
227
2
11

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(253 citation statements)
references
References 43 publications
13
227
2
11
Order By: Relevance
“…These emotions have an impact on how we evaluate decision outcomes (e.g. Inman et al, 1997). And ® nally, this impact of regret is taken into account before we decide, and thus may play an important role in determining what we choose (a detailed account of this in¯uence is provided later in this article).…”
mentioning
confidence: 99%
“…These emotions have an impact on how we evaluate decision outcomes (e.g. Inman et al, 1997). And ® nally, this impact of regret is taken into account before we decide, and thus may play an important role in determining what we choose (a detailed account of this in¯uence is provided later in this article).…”
mentioning
confidence: 99%
“…These emotions are more utilitarian, that is, they are more related to the hedonic value of decision outcomes or events. This presumably is why disappointment and (in particular) regret have attracted so much attention in research on individual decision-making (see e.g., Beattie et al, 1994;Bell, 1982Bell, , 1985Gull, 1991;Kelsey, á Schepanski, I991;Inman, Dyer, 8c Regrer und disuppoimnrenr 3 Jia, 1997;Inman, á McAlister, 1994;Janis á Mann, 1977;Josephs, Larrick, Steele, á Nisbett, 1992;Larrick, 8r. Boles, 1995;Loomes 8c Sugden, 1982, 1986, 1987Mellers, Schwartz, Ho,~Ritov, 1997;Richard, van der Plig[, á de Vries, 1996;Ritov, 1996;Ritov, 8c Baron, 1995;Taylor, 1997;van Dijk, 8c van der Pligt, 1997;Zeelenberg et al, I996;Zeelenberg, 8c Beattie, 1997;Zeelenberg, van der Pligt, óc Manstead, nt press).…”
mentioning
confidence: 99%
“…2 Research has shown that manipulations of feedback influence the levels of experienced regret or its positive counterpart (see, for example, Boles & Messick, 1995;Inman, Dyer & Jia, 1995;Ritov & Baron, 1995). Thus, feedback should also affect anticipated regret, and consequently decision making.…”
mentioning
confidence: 99%